2016
DOI: 10.1177/1475240916635896
|View full text |Cite
|
Sign up to set email alerts
|

Why offer the International Baccalaureate Middle Years Programme? A comparison between schools in Asia-Pacific and other regions

Abstract: The International Baccalaureate (IB) has become a powerful educational brand by developing a reputation for combining progressive approaches with academic rigour. This can be identified by the growing number of schools adopting IB programmes globally and especially in the IB Asia-Pacific region. As part of this trend, the IB Middle Years Programme (MYP), aimed at students between 11 and 16 years old, has expanded significantly in recent years. However, in Asia-Pacific, the MYP remains less popular relative to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…Another four studies in our sample included participants across the globe, without specifying particular countries. One of these studies, by Wright, Lee, Tang and Tsui (2016), included participants from 54 countries. In terms of research design and methodology, 58% of the articles were qualitative, 22% were quantitative and 20% utilized mixed methods.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another four studies in our sample included participants across the globe, without specifying particular countries. One of these studies, by Wright, Lee, Tang and Tsui (2016), included participants from 54 countries. In terms of research design and methodology, 58% of the articles were qualitative, 22% were quantitative and 20% utilized mixed methods.…”
Section: Resultsmentioning
confidence: 99%
“…As described earlier, the PYP and MYP are curriculum and pedagogical frameworks; the DP, on the other hand, structures its curricular content offerings and is externally assessed (Hallinger et al, 2011). Many IB teachers and Coordinators across the globe value the opportunity provided by the PYP and MYP to develop their own content, as reported by 71% of participants in the large cross-national study conducted by Wright et al (2016). Using the same dataset, Hallinger et al (2011) found that most participants perceived the structured curricular frameworks of the DP challenging.…”
Section: Impacts On Teachers and Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…These values are instilled through the IB's Learner Profile, a value system aiming to encourage students to become caring, principled, inquiring, reflective, and openminded, among other traits (Rizvi et al, 2014). The MYP's core concepts of communication, intercultural awareness, and holistic learning are said to develop the "whole person" and not just focus on academic content (Wright, Lee, Tang, & Tsui, 2016).…”
Section: Features Of the Mypmentioning
confidence: 99%
“…Despite its original aim to provide an internationally standardised education system, it does not escape opposition and criticism. As Wright, Lee and Tang (2016) point out, IB schools focus on cultivating groups of highly competitive students for entering elite higher education institutions. In addition, other critics assert that students' minds may be shaped towards globalism; that is, if students fail to submit to a 'globalist' way of thinking for the examinations, their chances in obtaining adequately high scores to enter elite schools is compromised (Mathews, 2001).…”
Section: Introductionmentioning
confidence: 99%